1997
DOI: 10.1179/imr.1997.42.5.206
|View full text |Cite
|
Sign up to set email alerts
|

Structure of non-graphitising carbons

Abstract: Despite many years of research, the detailed atomic structure of many important carbon materials remains poorly understood. In particular, the structure of those carbons which can not be transformed into graphite by high temperature heat treatment has never been clearly established. These non-graphitising carbons are of considerable commercial importance in a variety of fields, and a better understanding of their structure is clearly needed. Recently, it has been suggested that non-graphitising carbons may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(101 citation statements)
references
References 40 publications
2
83
0
Order By: Relevance
“…Moreover, according to theoretic calculations of the STW defect in a flat graphene two characteristic Raman modes at 1122 and 1173 cm -1 are predicted [39]. We assume that the D4 and D5 peaks observable here for the glassy carbons can also come from the vibrations of carbon atoms in non-hexagonal rings such as STW defects which are considered as the reason of the fullerene-like structure of glassy carbons [6][7][8].…”
Section: Correlation Of First-and Second-order Raman Peaks Behavior Wmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, according to theoretic calculations of the STW defect in a flat graphene two characteristic Raman modes at 1122 and 1173 cm -1 are predicted [39]. We assume that the D4 and D5 peaks observable here for the glassy carbons can also come from the vibrations of carbon atoms in non-hexagonal rings such as STW defects which are considered as the reason of the fullerene-like structure of glassy carbons [6][7][8].…”
Section: Correlation Of First-and Second-order Raman Peaks Behavior Wmentioning
confidence: 76%
“…The most recent studies have suggested that glassy carbons have a fullerene-related structure. Such model of the structure, proposed by Harris [2,[6][7][8], consists of broken and imperfect fullerene fragments in the form of curved sp 2 -bonded graphene-like planes, which can be multilayered and which often surround closed pores. The presence of curvature has been attributed to the topological defects in the form of non-hexagonal carbon rings such as pentagons and heptagons that were directly observed by the high-resolution transmission electron microscope (HRTEM) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are highly sought after as they provide a visual representation of the structure and enable direct simulation of gas adsorption and other properties. [11,12] These models, which overlap with nanoporous carbons, can be divided into two groups: geometric models and simulation models. Geometric models are highly idealized and are often constructed by hand.…”
Section: Introductionmentioning
confidence: 99%
“…The morphologies of the native and the pyrolized fibers were investigated by ESEM. [20] Fourier-transform infrared measurements of the untreated bacterial nanocellulose and samples pyrolized at 1000 °C and 1500 °C under N 2 are shown in Figure 2. The adsorption isotherms of Argon sorption measurements for two different BNC samples treated at 800 °C and 1500 °C under N 2 atmosphere and another sample treated at 1250 °C under Ar atmosphere were recorded (see Figure A in ESI).…”
Section: Results and Discussion P-bncmentioning
confidence: 99%